Efficacy of EGFR-TKI Plus Chemotherapy or Monotherapy as First-Line Treatment for Advanced EGFR-Mutant Lung Adenocarcinoma Patients With Co-Mutations - Yang, Zhengyu; Chen, Ya; Wang, Yanan; Wang, Shuyuan; Hu, Minjuan; Zhang, Bo; Han, Baohui (Frontiers in Oncology, 2021)
Background: Co-mutations was associated with poor responce to EGFR-TKIs. First-generation EGFR-TKIs combined with chemotherapy was reported to be more effective than TKIs alone in advanced lung adenocarcinoma patients. Objective: This retrospective study aimed to explore whether EGFR-mutant patients with co-mutations can benefit from EGFR-TKIs plus chemotherapy. Patients and Methods: We retrospectively collected data of 137 EGFR-mutant patients with advanced lung adenocarcinoma who underwent next-generation sequencing in our hospital in 2018. Among them, 96 were treated with EGFR–TKIs alone and 41 received EGFR–TKIs plus chemotherapy. We analyzed the progression-free survival (PFS) of patients with co-mutations using different treatments. Results: Concurrent TP53 mutations, especially exon 4 and 6, were associated with a markedly shorter time to progression on EGFR-TKI monotherapy (11.4 months vs. 16.6 months, P=0.003), while EGFR–TKIs plus chemotherapy would benefit those patients more (with TP53: 11.4 months vs. 19.1 months, P=0.001, HR=0.407; without TP53: 16.6 months vs. 18.9 months, P=0.379, HR=0.706). The incidence of T790M after resistance was equal in patients treated with different treatments (53% vs. 53%, P=0.985). Conclusions: In our study, concurrent TP53 mutations were found to be risk factors for EGFR-TKI monotherapy, but TKI combined with chemotherapy could eliminate this heterogeneity.